Recovering Discrete Delayed Fractional Equations from Trajectories - Lizama-Yanez, C (John Wiley and Sons Ltd, 2023)
We show how machine learning methods can unveil the fractional and delayed nature of discrete dynamical systems. In particular, we study the case of the fractional delayed logistic map. We show that given a trajectory, we can detect if it has some delay effect or not and also to characterize the fractional component of the underlying generation model. © 2023 The Authors. Mathematical Methods in the Applied Sciences published by John Wiley & Sons Ltd.